Ebselen as a potent covalent inhibitor of New Delhi metallo-β-lactamase (NDM-1)1. Issue 46 (11th June 2015) - Chiou, Jiachi; Wan, Shengbiao; Chan, Kin-Fai; So, Pui-Kin; He, Dandan; Chan, Edward Wai-chi; Chan, Tak-hang; Wong, Kwok-yin; Tao, Jiang; Chen, Sheng
<x xml:space="preserve">Abstract</x> We identified a potent NDM-1 inhibitor that formed a S–Se bond with the Cys221 residue at the active site, thereby exhibiting a new inhibition mechanism with broad spectrum inhibitory potential.